The development of website-based encyclopedia media on laboratory equipment material for laboratory engineering courses - AR, Nurfitri; Jamilah, Jamilah; Syahriani, Syahriani; Syamsul, Syamsul (JPBIO (Jurnal Pendidikan Biologi), 2024)
The importance of mastering laboratory equipment for Biology Education students encourages the development of a website-based encyclopedia as an interactive and easily accessible learning resource. This study aims to determine the characteristics of the media, the level of validity, and the level of practicality of the website-based encyclopedia on the material of introduction to laboratory equipment as support for laboratory engineering courses in the Biology Education Study Program, UIN Alauddin Makassar. The study was a research and development (R&D) based on the ADDIE development model, which included five steps: analyze, design, develop, implement, and evaluate. The results showed that the website-based encyclopedia media on laboratory equipment introduction material for the laboratory engineering course in the Biology Education Study Program UIN Alauddin Makassar has first-rate characteristics with an average expert validator rating of 100%. The media has a validity level of 3.66 means a very valid category. The media's level of practicality, as assessed by both students and lecturers, fell into the very high criteria, with a rating of 3.57 from students and 3.62 from lecturers. Therefore, the website-based encyclopedia media for introducing laboratory equipment is suitable and recommended for integration into the learning process.